Improved antenna range characterisation using redundant measurements - Smith, D.; Davidson, David; Bester, A. (2015)
© 2015 IEEE. The indoor antenna range at Stellenbosch University was substantially modernised during a recent upgrade. Now, this antenna range contains five automated motion stages, plus one manual stage, that facilitate redundant planar and spherical near-field measurements using an integrated system. In this paper, this capability is used to investigate the effect of potential sources of reflection in the range.